Early Detection Of Insulin Resistance In Patients With Paranoid Schizophrenia Receiving Antipsychotic Therapy - Romash, I. (Psychiatry, Neurology and Medical Psychology, 2016)
The article deals with the problem of insulin resistance, which is today considered a key aspect of the metabolic syndrome. The aim of our study was to investigate the effect of therapy classical and atypical neuroleptics on indicators of insulin resistance in patients with paranoid schizophrenia. During the study ,we found, that taking atypical neuroleptics for a long period, promotes infringement of carbohydrate metabolism. This reflected significant growth of blood glucose, immunoreactive insulin, postprandial glycemia, index NOMA-IR that are informative for the verification of an abnormal carbohydrate metabolism, insulin resistance and detection of type II diabetes in patients with paranoid schizophrenia who protractedly taking antipsychotics.